(untitled) (Eurasian Journal of Ecology, 2016)
It was determined genotoxic effects of asymmetrical dimethylhydrazine (UDMH) on barley seeds. With increasing concentration of UDMH was a statistically significant increase in aberrations in comparison to the control. The range of structural abnormalities of chromosomes was introduced as chromatid aberrations, chromosome types and izolokus breaks and microfragments. This indicates the possibility of damage genetic material in all stages of the cell cycle.